The Effectiveness of Problem-Based Learning Assisted by Articulate Storyline Interactive Students' Critical Thinking Skills - Nurhasanah, Mia; Suprapto, Purwati Kuswarini; Ardiansyah, Ryan (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
This study aims to reveal the impact of a problem-based learning model assisted by articulate storyline interactive media on high school biology students' critical thinking skills. This research was conducted in April-July 2023. The research method used was a quasi-experiment with a nonequivalent control group design. The population is all grade X science students (grade X IPA) of SMA Negeri 1 Kawali, West Java in the 2022/2023 school year as many as 6 classes. The sampling technique used was the purposive sampling technique, with grade X IPA 1 class as the experimental class and X IPA 3 as the control class each containing 36 students. The data collecting instrument is a critical thinking skill test consisting of 13 description questions that had gone through validity and reliability tests with the results of the instrument validity test, namely eight significant questions and five very significant questions, and the reliability score r = 0.84 including the high category. The data analysis technique used was the one-way ANOVA test at a significance level of 0.05. The average N-gain score of critical thinking skills of the experimental class is 0.45 (medium) higher than the control class which is 0.19 (low). Based on the results of testing the research hypothesis, it can be concluded that there is an effect of a problem-based learning model assisted by articulate storyline interactive media on critical thinking skills at a significance level of 0.000. The theoretical implication is that critical thinking skills can be improved by using a problem-based learning model assisted by interactive learning media so that the problem-based learning model assisted by articulate storyline interactive media can be used as a teaching method to improve critical thinking skills.